Tobacco Harm Reduction Approach in Clinical Practice: A Qualitative Study among Multi-Specialty Healthcare Professionals in an Indian Metropolitan City - Sree T Sucharitha; Aravind Manoharan; Pradeep Rangasamy; Balaji SM; Hari M Krishnan; Jeevanandam Subramanian (Medsci Publications, 2022)
Background:Tobacco harm reduction when advocated by care providers as continuum of care towards the goal of tobacco cessation might result in long-term abstinence than it is currently seen. This study aimed to qualitatively explore the healthcare professionals approach and self-reported practices related to tobacco harm reduction and smoking cessation. Methods: A purposive sample (N=36) of multi-specialty healthcare professionals providing tobacco related cessation services at six private medical teaching institutes were engaged in semi-structured qualitative interviews between July 2020 and October 2020 in Chennai. Results: The results indicated that majority of the healthcare professional's lack conceptual understanding about tobacco harm reduction. Harm reduction was practised and nicotine replacement therapy was prescribed by psychiatrists in this study. Majority of the healthcare professionals were found to have misconceptions that promoting harm reducing practices instead of cessation might result in continued addiction to nicotine products among the clientele. Conclusions: The findings reveal that tobacco harm reduction remains an under-utilized clinical practise in Indian setting due to knowledge and awareness gaps among multi-specialty healthcare professionals. Improved sensitization through continuous medical education updates is needed to inform effective clinician-affirmative tobacco harm reduction practices.